Legality of Bitcoin in the Perspective of Fiqh Muamalah - Achmad Napis Qurtubi; Efendi Sugianto; Muhammad Umar Kelibia (Westscience Press, 2024)
This study investigates the legality of Bitcoin from the perspective of Fiqh Muamalah through qualitative analysis and literature review. Fiqh Muamalah, an Islamic jurisprudential framework, regulates economic transactions according to Sharia law. The research examines whether Bitcoin, as a digital currency, aligns with Islamic legal and ethical standards by analyzing scholarly articles, religious texts, and fatwas issued by Islamic scholars. Key considerations include Bitcoin's nature as a currency, its speculative role, and potential for illicit activities. Findings reveal diverse scholarly opinions, with some viewing Bitcoin as permissible under specific conditions, while others raise concerns about its speculative nature and lack of intrinsic value. This study aims to provide comprehensive insights into Bitcoin's legality within Fiqh Muamalah, offering valuable information for policymakers, financial institutions, and Muslim investors.